2007
DOI: 10.1371/journal.pbio.0050305
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity in Rat Barrel Cortex Underlying Texture Discrimination

Abstract: Rats and mice palpate objects with their whiskers to generate tactile sensations. This form of active sensing endows the animals with the capacity for fast and accurate texture discrimination. The present work is aimed at understanding the nature of the underlying cortical signals. We recorded neuronal activity from barrel cortex while rats used their whiskers to discriminate between rough and smooth textures. On whisker contact with either texture, firing rate increased by a factor of two to ten. Average firi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
180
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(190 citation statements)
references
References 55 publications
(77 reference statements)
9
180
0
Order By: Relevance
“…This response pattern may be tuned to the timing of chunks of vibrotactile signals [e.g., stick-slip events, instances of high acceleration in the vibrotactile signal brought about by interplay of surface and whisker mechanics (Arabzadeh et al, 2005;Wolfe et al, 2008;Ritt et al, 2008)] coming in at the rhythm of sequential whisker strokes. One study reported that, indeed, rats use repetitive whisking against a texture to reach a decision, mostly 1-3 consecutive whisks (von Heimendahl et al, 2007). Assuming a whisking frequency of ϳ7 Hz and touch times of 50 ms per single whisk (von Heimendahl et al, 2007) these strips of data would be integrated using the short time constant found in the present study and then separated by ϳ100 ms to the next touch time by suppression of signal flow in barrel cortex.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This response pattern may be tuned to the timing of chunks of vibrotactile signals [e.g., stick-slip events, instances of high acceleration in the vibrotactile signal brought about by interplay of surface and whisker mechanics (Arabzadeh et al, 2005;Wolfe et al, 2008;Ritt et al, 2008)] coming in at the rhythm of sequential whisker strokes. One study reported that, indeed, rats use repetitive whisking against a texture to reach a decision, mostly 1-3 consecutive whisks (von Heimendahl et al, 2007). Assuming a whisking frequency of ϳ7 Hz and touch times of 50 ms per single whisk (von Heimendahl et al, 2007) these strips of data would be integrated using the short time constant found in the present study and then separated by ϳ100 ms to the next touch time by suppression of signal flow in barrel cortex.…”
Section: Discussionmentioning
confidence: 70%
“…One study reported that, indeed, rats use repetitive whisking against a texture to reach a decision, mostly 1-3 consecutive whisks (von Heimendahl et al, 2007). Assuming a whisking frequency of ϳ7 Hz and touch times of 50 ms per single whisk (von Heimendahl et al, 2007) these strips of data would be integrated using the short time constant found in the present study and then separated by ϳ100 ms to the next touch time by suppression of signal flow in barrel cortex. In future studies it has to be worked out whether neuronal activity generated by active whisking (Fanselow and Nicolelis, 1999;Hentschke et al, 2006) may recruit memory systems, not available to our passively detecting rats, that in addition integrates information acquired across repetitive whisker strokes.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Freely moving rodents can discriminate the roughness of textures (Guić-Robles et al, 1989;Carvell and Simons, 1990;von Heimendahl et al, 2007) and the widths of apertures (Krupa et al, 2001). Rodents also accurately judge the distances to platforms ("gap crossing") (Hutson and Masterton, 1986;Celikel and Sakmann, 2007) and the relative distance of two objects (Knutsen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This form of active sensation has been compared with digital palpation and microsaccadic eye movements in primates Kleinfeld et al, 2002). A consequence of the rhythmical nature of whisking is that neuronal activity in the primary somatosensory (barrel) cortex varies rhythmically in synchrony with whisker movement and contact against obstacles (Fee et al, 1997;Crochet and Petersen, 2006;von Heimendahl et al, 2007). The vibrissal motor cortex, which controls whisker movement (Brecht et al, 2004), is interconnected with both cortical and subcortical somatosensory structures (Miyashita et al, 1994), and activity in the motor cortex is also modulated synchronously with whisker movement (Kleinfeld et al, 2002;Chakrabarti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%